My son! my son! - Smith, Elton Edward (Edinburg, New York : The Pentland Press Limited, 1999)
MY SON, MY SON is bestselling British author Howard Spring's multigenerational portrait of a relationship between father and son.
Chapter1. Brother -- Chapter2. Son -- Chapter3. Exile -- Chapter4. Rebel -- Chapter5. Dead .
Keywords: POETRY